Does PRGF Work? A Prospective Clinical Study in Dogs with A Novel Polylactic Acid Scaffold Injected with PRGF Using the Modified Maquet Technique - Victoria Valiño-Cultelli; Óscar Varela-López; Antonio González-Cantalapiedra (Animals, 2021)
Tibial tuberosity advancement is a surgical technique to restore the dynamical stability in the knee by advancing the insertion of the patellar ligament, for which it is necessary to advance the tibial crest, being maintained in the desired position usually by a cage and metallic implants. The purpose of this study was to replace the cage with a polylactic acid biodegradable scaffold designed for each patient by 3D printing, inserting platelet-rich in growth factors (PRGF) to demonstrate its osteoinductive properties. To this end, we used the modified Maquet technique to reduce the amount of metal to a minimum. Fifty-three dogs finished the study. The control and PRGF groups did not present any statistically significant differences in terms of ossification degree (p > 0.001) but they demonstrated satisfactory ossification compared to previous publications, although in the PRGF group three of the scaffolds suffered complete reabsorption. The PRGF and control groups did not show any statistically significant differences in terms of lameness degree (p > 0.001). However, the PRGF group showed at the first control some analgesic and anti-inflammatory properties but they were not enough for reducing the functional recovery time in a significant way. The PRGF group did not show any complications or negative results associated with their use.